The aggregate effects of sectoral shocks in an open economy - Philippe Andrade; Martin Arazi; Viacheslav Sheremirov (Federal Reserve Bank of Boston, 2023)
We study the aggregate effects of sectoral productivity shocks in a multisectoral New Keynesian open-economy model that allows for asymmetric input-output linkages, both within and between countries, as well as for heterogeneity in sectoral Calvo-type price stickiness. Asymmetries in the international production network play a key role in the model's ability to produce large domestic effects of foreign sectoral supply shocks and large differential effects of domestic shocks and global shocks. Larger trade openness and substitutability between domestic inputs and foreign inputs can also significantly amplify the effects of foreign and global sectoral shocks on domestic aggregates. In comparison, sectoral heterogeneity in price stickiness does not materially amplify the domestic responses to productivity shocks that originate abroad.
Keywords: E12; E31; F41; F44; 330; International input-output linkages; open-economy New Keynesian model; sectoral shocks